2015
DOI: 10.1016/j.imbio.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 antagonist attenuates atherogenesis in LDL receptor-deficient mice with diet-induced type 2 diabetes

Abstract: Although a large number of studies have well documented a key role of toll-like receptor (TLR)4 in atherosclerosis, it remains undetermined if TLR4 antagonist attenuates atherogenesis in mouse model for type 2 diabetes. In this study, we induced type 2 diabetes in low-density lipoprotein receptor-deficient (LDLR−/−) mice by high-fat diet (HFD). At 8 weeks old, 20 mice were fed HFD and 20 mice fed regular chow (RC) for 24 weeks. In the last 10 weeks, half HFD-fed mice and half RC-fed mice were treated with Rhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…The limitations of the human studies with existing anti-cytokine reagents were recently reviewed in an excellent article (230). There are also exciting, but not yet fully exploited, possibilities by antagonizing lipid-sensing pathways, i.e., using TLR4 antagonists (231) or PKR inhibitors (232) to alleviate inflammation along with other beneficial effects associated with the target functions. In these areas, studies in humans are also highly limited at the moment.…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…The limitations of the human studies with existing anti-cytokine reagents were recently reviewed in an excellent article (230). There are also exciting, but not yet fully exploited, possibilities by antagonizing lipid-sensing pathways, i.e., using TLR4 antagonists (231) or PKR inhibitors (232) to alleviate inflammation along with other beneficial effects associated with the target functions. In these areas, studies in humans are also highly limited at the moment.…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…Slides were fixed in 10% of formaline for 10 minutes, stained with Harris modified hematoxylin (Fisher Scientific, Pittsburgh, PA) for 10 minutes and then rinsed in deionized water. Histological analysis of atherosclerotic lesions was performed as described previously 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis was performed as described previously 13 with anti-F4/80 (Bio-Rad Laboratories, Inc., Hercules, CA), anti-CD68 (AbD Serotec, Raleigh, NC) and anti-intercellular adhesion molecule (ICAM-1) antibodies (Santa Cruz Biotechnology, Inc. Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, polymorphisms in tlr4 have also been associated with psoriatic arthritis 34 and the development of rheumatoid arthritis 35 . Although recent mouse studies have shown that TLR4 antagonists can reduce atherogenesis in mice with type‐2 diabetes 36 …”
Section: Toll‐like Receptors and Diseasementioning
confidence: 99%